Pemanfaatan Tanaman Bambu dan Kaliandra untuk Perkuatan Lereng sebagai Upaya Mitigasi terhadap Longsor di Desa Sinarresmi Sukabumi: Utilization of Bamboo and Kaliandra Plant for Slope Reinforcement as a Mitigation Effort against Availability in Sinarresmi Village, Sukabumi - Ruwaida Zayadi; Sih Andayani; Etty Indrawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The PKM program, with the theme of community empowerment in sustainable environmental management with the title